Anterior superior iliac spine distraction for severe and recalcitrant diabetic foot ulcers. Issue 2 (February 2023) - Liu, Yingliang; Jiang, Changhai; Zhang, Xu; Ma, Bingshu; Ding, Yanfen; Jin, Yanhong; Liu, Yanjun; Li, Linhong; Zhao, Chenglong
Abstract: Purpose: The study aimed to introduce anterior superior iliac spine distraction to treat severe and recalcitrant diabetic foot ulcers. For comparison, we also included another group of diabetic foot ulcers treated with proximal tibial cortex transverse distraction. Methods: From February 1998 to February 2020, 87 patients (87 feet) with severe and recalcitrant diabetic foot ulcers were treated. The mean age of patients at surgery was 64 years (range, 47 to 87 years). The severity of the narrowed artery was assessed using the ankle-brachial index test. For comparison, another group of 91 patients (91 diabetic foot ulcers) treated with proximal tibial cortex transverse distraction was included. Results: The mean preoperative ankle-brachial indexes of the two groups were 0.41±0.07 and 0.39±0.05 (OR 0.65 [95% CI -0.77 to 1.58]; P=0.62), respectively. The mean preoperative limb pain was 3.42±2.84 cm and 3.52±3.11 cm (OR 1.54 [95% CI -077 to 1.35]; P=0.083), respectively. At the 2-year follow-up visit, ulcers healed in 72 (83%) and 74 (81%) patients, respectively (P=0.188). The mean postoperative limb pain was 0.52±0.23 cm and 0.49±0.41 cm (OR 2.32 [95% CI -0.27 to 1.66]; P=0.078), respectively. Pin-site infection occurred in 2 patients and 8 patients (P=0.09), respectively. Ulcer recurrence occurred in 13 (15%) patients and 15 (16%) patients (P=0.205), respectively. Conclusions: Anterior superior iliac spine transverse distraction may be an effective alternative treatment for severe and recalcitrant diabetic foot ulcers. It may be associated with fewer distraction-site complications than proximal tibial cortex transverse distraction. Level of evidence: Therapeutic study, Level IIa.